5-Fluorouracil and Cyclophosphamide modify functional activity in submandibular gland of rats. - Evelin Bachmeier; María Marcela López; Jorge Alberto Linares; Mabel Noemí Brunotto; Marcelo Adrián Mazzeo (Journal of Oral Research, 2019)
Objective: Chemotherapy treatment against cancer produce systemic toxicities, among which are those related to important structures of the stomatognathic system and its functional activity. 5 Fluorouracil (5-FU) and cyclophosphamide (Cf) are drugs widely used in solid tumors and in bone marrow transplantation, respectively. The objective of this work was to evaluate the toxicity of these drugs regarding functional activity of the submandibular glands, by measuring the percentage of glycogen consumption in two experimental models. Material and Methods: 84 male Wistar rats aged three months were used, housed in individual cages, with controlled temperature and lighting and ad libitum diet. They were divided into four experimental groups: 1) Control (C); 2) Treated with 5-FU+leucovorin (LV) at 20 and 10mg/Kg of body weight respectively for five consecutive days; 3) treated with Cf i.p. at 50mg/Kg of body weight for two consecutive days; and 4) rats with paired feeding (PF): for five and two days respectively, the amount administered resulted from the average of the ingested food of groups 2 and 3. Both submandibular glands were excised. The submandibular glycogen concentration was analyzed at initial time (t0) and after 60 minutes of mechanical stimulation (t60). Results: the average variation changed significantly between time 0 and 60 in the groups C and PF. (p-value=0.0001), the 5-FU + LV treatment group had an average concentration higher at t0 than groups C and PF, without significant consumption at T60. While group Cf showed a lower average concentration at time 0 with respect to groups C and PF, without significant consumption at T60. Conclusion: 5-FU+LV and Cf affect the metabolism of carbohydrates, decreasing the use of glycogen as a metabolic substrate. In the present experimental model, the toxicity of these drugs affected the functional activity of the submandibular gland.